(3eNJUQ aj Yde GdCNdGbs - (3YHO GdQMef Hf CMeO Hf YHO GdZaGQ, CHh GdaVd, nYoVO GdOjf GdEjLj,J (B756 (3g` s ((3eMeO Hf CMeO GdgGja s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fhGdg hHYO agPG eNJUQ ai Yde GdCNdGb QJjHg Ydi CQHY ebGdGJ GdebGdI GdChdi ai GdfXQi efg GdNdb edcI JUOQ YfgG GdCbhGd GdfaSGfjI s
(3BNQgG (B:s
(3hGdEMSGf Edjge hbVGA MhGFL GdfGS eG Cecf hdRhe GdYGOGJ ef GdJYGRi hGdJgGfi hGdYHGOGJ hEXgGQ GdaQM daQMge hGdZe dZege HMjK dG jNQL Edi MO GdfaGb hGddg JYGdi CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B474) s
Keywords: (3GdeLGejYs